Th. Adorno and the German Philosophy - Valentinavičius, Virginijus (Problemos, 1986)
The place of Th. Adorno’s ideas in the history of the German philosophy is discussed. T. Adorno’s philosophy is claimed to be a conservative opposition to the modem German philosophy. The origins of this conservatism are traced back to Hegel’s dialectics and the early forms of existentialism. It is argued that Th. Adorno made the contradiction between the two less striking by nonphilosophical means.